Active acoustic cloaking of cylindrical shells in low Mach number flow. (4th August 2020) - Kerferd, Briscoe; Eggler, Daniel; Karimi, Mahmoud; Kessissoglou, Nicole
Abstract: The vibro-acoustic response of a two-dimensional cylindrical shell in low Mach number flow is herein derived. The analytical model takes into account the structural elasticity and coupling of the shell vibration with its interior and exterior acoustic fields in the presence of a moving fluid. The cylindrical shell is modelled using Donnell-Mushtari theory. Taylor transformations are employed to transfer the convected wave equation into the ordinary wave equation which was then solved using scattering theory. Three excitation cases corresponding to a plane wave, an external monopole source and a radial point force applied directly to the shell are considered. Shell circumferential resonances and interior acoustic resonances are identified. Two active control strategies are then applied to acoustically cloak the cylindrical shell at its acoustic and structural resonances. The first control approach employs acoustic control sources in the exterior fluid domain. In the second approach, control forces are applied to directly excite the elastic shell, whereby the structural response is actively modified to manipulate the scattered and radiated acoustic fields arising from plane wave excitation of the shell. Results show that the second approach is superior in terms of both reduced control effort and cloaking of the global exterior domain. For both control approaches, the performance of the active cloak is shown to deteriorate if the convected flow field is not accounted for in the control process. Highlights: Vibro-acoustic responses of a cylindrical shell in potential flow are derived. Structural and acoustic source excitation cases are modelled. Effect of fluid flow on the structural and acoustic resonances are observed. Active acoustic cloaking of the shell in a moving fluid is presented.